Pendampingan Guru MI dalam Penerapan Model Inquiry untuk Meningkatkan Kemampuan Pemecahan Masalah - Suryani, Suryani; Utomo, Dwi Prio (Universitas Pahlawan Tuanku Tambusai, 2026)
Mathematics learning in Islamic Elementary Schools (MI) still faces challenges in the form of low student problem-solving skills and limited teacher competency in implementing innovative learning models. This community service activity aims to improve the competence of MI teachers through mentoring the implementation of the Inquiry-Based Meaningful Learning Model in mathematics learning. The implementation methods include workshops, classroom supervision, reflection, and continuous improvement. The results of the activity show an increase in teacher pedagogical competence, especially in designing learning tools, implementing inquiry stages systematically, and facilitating student investigative activities. Quantitatively, students' problem-solving abilities increased from an average of 55 in the pretest to 78 in the posttest. Qualitatively, students showed increased participation, independence, and the ability to explain problem-solving strategies. Thus, teacher mentoring in implementing the inquiry-based meaningful learning model effectively improves the quality of mathematics learning in MI and is recommended for continued implementation in other madrasas.